Strengthening National Insight for the Younger Generation in the Reading Community in the City of Serang - Saefulloh, Febri; Ayuni, Mela Sri; Fajrudin, Lili; Zulfiah, Rifda Cita (International Journal of Education, Information Technology, and Others, 2024)
This study aims to determine the strengthening of national insight for the young generation of Serang City. This type of research is descriptive qualitative data collection was carried out by means of observation, interviews, and documentation. The informants in this study numbered 10 people, community leaders and members. The results of this study indicate that the community plays a role in strengthening national insight for the younger generation in Serang City. Members are very enthusiastic about the programs available in the community. This can judge from the changes in behavior of each member, they always participate actively. in the community program. From this activity, the chairman stated that the program organized by the community is able to provide insight into strengthening nationality for the younger generation. In developing the strengthening of insight nationality members are able to implement the programs that have been implemented in community life. The younger generation is more active in implementing its duties as a youth to become an ideal youth after the program took place, the members got to know each other's characters better. through favorite programs such as cheerful week, community birthday, big day competitions (coloring competition for national figures, independence day, heroes day, national education day) and exercise activities held on weekends. There are efforts and obstacles experienced by the community. The efforts are the headquartersis self-owned, there is assistance from the community and institutions Indonesian and regional and city libraries. While the constraints are that there is a small number of members, limited budget and insightful programs monotonous nationality.